Variasi Konsentrasi Span-80 Dan pH Fasa Eksternal pada Ekstraksi Ion Timbal(II) Dengan Metode Emulsi Membran Cair - Djasman, Syamsiar Masgul; Hamzah, Baharuddin; Husnia, Husnia (Universitas Tadulako, 2014)
A research on the extraction of lead(II) ion has been done using emulsion liquid membrane technique. This research used a laboratory experiment method by using benzoyl acetone as a carrier, paraffin liquid as the membrane, a solution of nitric acid as an internal phase, Span-80 as a surfactant, and lead(II) solution as the sample. This research was conducted to determine the optimum extraction condition of lead(II) ions in solution which includes the span-80 concentration variations (2 - 5%) and the pH of the external phase variations (2 – 4). Determination of the concentration of lead(II) ions in the external phase is done using a Spectro Direct. The results showed that the concentration of span-80 that produces a maximum extraction percentage is 3%. Moreover, the pH of the external phase which produces the maximum percentage extraction at pH 2 with extraction percentage of 74.36%.